A lifespan psychological perspective on solitude. (November 2022) - Hoppmann, Christiane A.; Pauly, Theresa
Solitude occurs from childhood to old age. In this special issue introduction, we offer a lifespan perspective on matters of solitude with the aim to point to pertinent issues in the field. We propose that solitude serves important functions that may vary across different times in life and that solitude needs to be considered in the context in which it occurs. In applying these lifespan developmental notions, we carve out some open questions that will help extend the current knowledge base including a consideration of issues regarding operational definitions of solitude. We also point to methodological challenges such as capturing processes that unfold on different timescales that need to be addressed to advance the field.